Copper-catalyzed enantioselective Sonogashira-type oxidative cross-coupling of unactivated C(sp 3)−H bonds with alkynes - Zhen-Hua Zhang (Nature Portfolio, 2019)
Enantioselective oxidative cross-coupling of unactivated C(sp 3)−H bonds and terminal alkynes is challenging. Here, the authors developed a copper/cinchona alkaloid catalyst for the asymmetric Sonogashira-type alkynylation of C(sp 3)-H bonds via radical intermediates.